Improved Approximate Expectation Propagation Massive MIMO Detector with Second-Order Richardson Iteration. (16th February 2022) - Deng, Qian; Chen, Xuehui; Fu, Wanting; Liang, Xiaopeng; Xie, Shilong; Shu, Feng; Wu, Yuan Yuan
Abstract : The expectation propagation (EP) detector achieves significantly better performance than the linear detectors (such as minimum mean squared error detector) in massive MIMO systems, which has drawn great attention recently. EP's approximation (EPA) algorithm simplifies the update formula of the EP algorithm by reexpressing the moment matching condition so that the number of matrix inversions in the EP algorithm is reduced to one. However, the expense is that the EPA algorithm requires higher accuracy for this inversion; otherwise, the bit-error-rate (BER) performance will suffer serious losses. To tackle this issue, the SORI iterative algorithm is introduced to obtain the high-precision result of this inversion to ensure the good BER performance of the EPA algorithm. First, the new expression of the SORI iterative algorithm is derived under the equivalent real-valued system. Second, the improved EPA-SORI algorithm is then introduced by the SORI algorithm, which is used to approximate the initial value of the EPA algorithm under the real-valued system. Finally, by designing the initial solution and the relaxation factor of the EPA-SORI iterative algorithm, the convergence rate can be quickly increased without increasing the complexity. Simulation and complexity results exhibit that in various massive MIMO system configurations, the proposed EPA-SORI algorithm can achieve the same BER performance as the Exact EP algorithm with significantly lower complexity. At the same time, compared with MMSE and the existing EPA algorithms, the proposed EPA-SORI algorithm has a better performance-complexity trade-off advantage, which is more obvious in scenarios with high modulation order and a large number of users.